Legal Discourse on Manpower During COVID-19 Outbreak - Richard Kennedy (LAW REFORM, 2020)
Covid-19 has become a global epidemic all around the world. All countries around the world have been completely struggled by this outbreak, including Indonesia. Economy crisis is something that could not be avoided. Naturally, workers, and entrepreneurs will be either directly or indirectly affected. Massive amount of companies has applied the regulation “Termination of Employment”, laid of the workers, and even deduction on wages payment. Workers have become vulnerable parties in this case because they do not have enough assurance. Article 164 (1) Act No. 3 of 2003 concerning Manpower indeed regulates the Termination of Employment regulation because of force majeure, however this law seems to be slightly unsuitably applied for this outbreak Covid-19 situation. Therefore, this study is aimed to do legal discoursing in which can both assure those workers and maintain the operation of business in this tight condition. Finally, Indonesia needs to return back to kinship culture and unity in diversity philosophy as stated in Pancasila to equalize the interests both for workers and employers. According to Article 33 (1) and (4) of 1945 Constitution of Republic Indonesia, it has been firmly stated that Indonesian economy should be organized as a common endeavor based upon the principles of the family system and conducted on basis of Pancasila democracy. Hence, government is expected to play the intermediary role in order to unify and even out interest of all parties. Law of Manpower need to be adjusted with some regulations about rights and responsibilities accommodate to workers, employers, and government in deal with epidemic outbreak.